ANALYSIS OF THE CONTRIBUTION OF THE PALM OIL COMMODITY PLANTATION SUB-SECTOR IN THE ECONOMY NORTH LABUHAN BATU REGENCY - Suleha Angrayana; Tuty Ningsih (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to analyze the contribution of the smallholder oil palm plantation subsector to the economy of North Labuhanbatu Regency. The analysis was conducted on the development of smallholder oil palm area, production, and productivity, the magnitude of its contribution to the regional economy, and the status of commodity superiority using the Location Quotient (LQ) and Dynamic Location Quotient (DLQ) methods. The study used a quantitative descriptive method with secondary data for the 2014–2024 period obtained from the Central Statistics Agency, the Plantation Service, and other relevant sources. The results showed that the area of smallholder plantations increased from 64,916 ha to 79,080 ha, production increased from 768,888 tons to 1,381,330 tons, and productivity increased from 11.84 tons/ha to 17.47 tons/ha during the study period. The average contribution of smallholder oil palm plantations to the agriculture, forestry, and fisheries subsector reached 29.33%, while its contribution to the Gross Regional Domestic Product (GRDP) of North Labuhanbatu Regency was 12.00%. The results of the LQ and DLQ analyses indicate that smallholder oil palm plantations are a basic commodity with comparative advantages and good development prospects. These findings indicate that smallholder oil palm plantations have a strategic role in supporting the economic growth of North Labuhanbatu Regency.